A case study in support of closure of bow shock current through the ionosphere utilizing multi-point observations and simulation - Dredger, Pauline M.; Lopez, Ramon E.; Hamrin, Maria (Frontiers in Astronomy and Space Sciences, 2023)
On the bow shock in front of Earth’s magnetosphere flows a current due to the curl of the interplanetary magnetic field across the shock. The closure of this current remains uncertain; it is unknown whether the bow shock current closes with the Chapman-Ferraro current system on the magnetopause, along magnetic field lines into the ionosphere, through the magnetosheath, or some combination thereof. We present simultaneous observations from Magnetosphere Multiscale (MMS), AMPERE, and Defense Meteorological Satellite Program (DMSP) during a period of strong By, weakly negative Bz, and very small Bx. This IMF orientation should lead to a bow shock current flowing mostly south to north on the shock. AMPERE shows a current poleward of the Region 1 and Region 2 Birkeland currents flowing into the northern polar cap and out of the south, the correct polarity for bow shock current to be closing along open field lines. A southern Defense Meteorological Satellite Program F18 flyover confirms that this current is poleward of the convection reversal boundary. Additionally, we investigate the bow shock current closure for the above-mentioned solar wind conditions using an MHD simulation of the event. We compare the magnitude of the modeled bow shock current due to the IMF By component to the magnitude of the modeled high-latitude current that corresponds to the real current observed in AMPERE and by Defense Meteorological Satellite Program. In the simulation, the current poleward of the Region 1 currents is about 37% as large as the bow shock Iz in the northern ionosphere and 60% in the south. We conclude that the evidence points to at least a partial closure of the bow shock current through the ionosphere.